Cambios morfológicos de la articulación temporomandibular en relación con el estado dental: un estudio con material cadavérico - García-L., José Domingo; Ballesteros-A., Luis Ernesto (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Objective: The purposes in this study were determine the size of structure of temporomandibular joint, the morphology of mandibular condile, the presence of osteoarthritis (OA) and determine the association between dental state and condile remodelation. Materials and methods: We studied one hundred twenty temporomandibular joints (MD, which were extracted from fresh cadavers trough medium craneal fossa approach. The cadavers were aged between twenty to eighty five years old with a dental state classified as dentulous, partially dentulous and edentulous. The muscles structures were resected in the articular blocks and their capsules were cut. After were evaluated the size of the articular components and the shape of the condile. Results: The size of the condyle was 1029 nun in the antero-posterior plane (A P) and 19.97 mm for the medium-lateral lenght (M-L). The size of the temporal component (mandibular fossa and articular tubercle) averages 19.23 mm for the A-P dimension and 2283 mm for the M-L diameter. The articular disk was measured at the level of the posterior band, middle zone and anterior band; the results of those measurements average 2.95, 0.70 and 1.68 mm. Round shape was predominant in superior part (42.5%), convex shape was observed in most cases in anteriorpart (471%). Dentulous cadavers had round condiles in superior part (52.7%) and in the rest part was founded others shapes. In partially dentulous, was predominant the elipsoide shape (40.8%), while round condiles had 36.6percentage. In the study, 39,2% joints had macroscopic signs of OA. We found OA in 22.2%,408% and 78.9% of dentulous, partially dentulous, and edentulous state respectivelly. Osteoarthritis was also observed in 48.1% from cadavers without bilateral inferior molarrest We demostrated stadistic asociation between OA and dental condition. (F<0.001). Conclusions: The size of the articular structures in this study is similar to those reported in different investigation have been made in contemporary population. Was found in mostofpartiallydentulous cadavers rernodelation condile and round shapes (no rernodelation)in dentulous cadavers. Didn’t found sipzificandy association between dental state and remodelation condile (P<0.16), although in many specimens with dental piece lost was observed thepredominance of remodelingshapes ofcondile. Was foundsignificantlyassociation between dental condition and osteoarthritis presence of temporomandibularjoint (p<0.00.1), we concluded that the lowernumbe_rs ofdental pieces have thehigherpossibilh y to develop OA ofthe TMJ.